(untitled) (AYUSHDHARA, 2024)
When a couple is unable to get pregnant after a year of regular, unprotected sexual intercourse, it is referred to as infertility. The problem is defined as the absence of an obvious cause for a couple’s infertility and the female’s inability to become pregnant after at least 12 cycles of unprotected sexual relations, or after six cycles in women over 35 who meet all standard evaluation criteria. Several drugs have been listed in Ayurvedic literature to treat infertility. We are presenting a primary infertility case here. The couple spent two years trying to become pregnant. After extensive physical and scientific testing to rule out the cause, the underlying cause was found to be unexplained. Ayurvedic formulations like Tablet Leptadan, Capsule Femigrow, Phalaghrita and Tarunikusumakar Churna were given continuously for 3 months. Her 3 months of Ayurvedic intervention resulted in the conception and she delivered a full term male baby weighing 2.5kg through lower segment caesarean section.